2015
DOI: 10.2147/dddt.s91299
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of cytogenetic biomarkers as a tool for assessment of radiation injury and evaluation of radiomodulatory effects of various medicinal plants – a review

Abstract: Systematic biological measurement of “cytogenetic endpoints” has helped phenomenally in assessment of risks associated with radiation exposure. There has been a surge in recent times for the usage of radioactive materials in health care, agriculture, industrial, and nuclear power sectors. The likelihood of radiation exposure from accidental or occupational means is always higher in an overburdened ecosystem that is continuously challenged to meet the population demands. Risks associated with radiation exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 142 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…In conclusion, previous studies on calcium sennosides, as a radioprotector, reported the amelioration of biochemical, immunological, and cytogenetic measurements after radiation exposure with limited percent (Ahmed et al, 2018;Jothi et al, 2015;Samarath, Samarathm, & Matsumoto, 2015;Shanmugasundaram et al, 2011;Yen & Chuang, 2000). Whereas the present study proofed that the synergetic effect of calcium sennosides with fennel seed extract showed a high improvement in all measurements.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, previous studies on calcium sennosides, as a radioprotector, reported the amelioration of biochemical, immunological, and cytogenetic measurements after radiation exposure with limited percent (Ahmed et al, 2018;Jothi et al, 2015;Samarath, Samarathm, & Matsumoto, 2015;Shanmugasundaram et al, 2011;Yen & Chuang, 2000). Whereas the present study proofed that the synergetic effect of calcium sennosides with fennel seed extract showed a high improvement in all measurements.…”
Section: Discussionsupporting
confidence: 80%
“…Plant parts such as fruits, roots, stem/bark, leaves, and medicinal herbs have been found to have antioxidant capacity due to the presence of phenolic compounds, vitamins, nitrogen compounds, terpenoids, and other metabolites. These compounds have been shown to possess antioxidant, immunostimulatory, and antimicrobial activity and to impart radioprotective effects (Samarth et al, 2015). Therefore, it has been found that F. margarita is a rich resource of bioactive compounds enriched with antioxidants more effective than those of citrus species (Tan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation causes structural chromosome aberrations. Thus, the systematic measurement of cytogenetic endpoints helps in the assessment of risks linked to radiation exposure [313]. The mechanism of damage is not yet fully explored.…”
Section: Cytogeneticsmentioning
confidence: 99%